2020
DOI: 10.1038/s41598-020-59041-z
|View full text |Cite
|
Sign up to set email alerts
|

A valuable computed tomography-based new diagnostic tool for severe chest lesions in active pulmonary tuberculosis: combined application of influencing factors

Abstract: The objective of the present investigation was to explore the influencing factors and value of computed tomography (ct) for diagnosing severe chest lesions in active pulmonary tuberculosis (AptB). this retrospective investigation included 463 patients diagnosed with APTB. Relevant clinical features were collected. patients were assigned to mild/moderate group or advanced group depending on the lesion severity on chest CT, severe chest CT lesion refers to the moderately dense or less diffuse lesion that exceeds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our results demonstrated that one risk factor for persistent severe inflammation in TB patients was a large cavity on chest CT, and patients with large cavities tended to show nonconversion of sputum cultures, similar to the findings of a previous report [13] . During the course of TB, a cavity is formed when an expanding granuloma ruptures, [14] and a cavity with a diameter of 4 cm or more is considered a severe lesion [11] . In general, CRP levels are increased in pulmonary TB patients with extensive lung tissue damage, as the pulmonary inflammatory process is influenced not only by the large population of TB bacilli but also by the presence of lung damage, which is associated with lung tissue inflammation [3] .…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our results demonstrated that one risk factor for persistent severe inflammation in TB patients was a large cavity on chest CT, and patients with large cavities tended to show nonconversion of sputum cultures, similar to the findings of a previous report [13] . During the course of TB, a cavity is formed when an expanding granuloma ruptures, [14] and a cavity with a diameter of 4 cm or more is considered a severe lesion [11] . In general, CRP levels are increased in pulmonary TB patients with extensive lung tissue damage, as the pulmonary inflammatory process is influenced not only by the large population of TB bacilli but also by the presence of lung damage, which is associated with lung tissue inflammation [3] .…”
Section: Discussionsupporting
confidence: 89%
“…Patients with a CRP level ≥9.0 mg/dL had a longer time until inflammation improvement than those with a CRP level <9.0 mg/dL (median (IQR) 20 days [13-43] vs 8 days [8][9][10][11][12][13][14], log rank test P < .001), and the hazard ratio was 2.37 (95% Cl: 1.70-3.30).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations